2013
DOI: 10.12693/aphyspola.124.11
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sliding Wear Behavior of Al2O3/SiC Particle Reinforced Aluminium Based MMCs Fabricated by Stir Casting Method

Abstract: Al2O3/SiC particulate reinforced metal matrix composites were produced by a stir casting process. The Al2O3/SiC powder mix was prepared by reaction of aqueous solution of aluminium sulphate, ammonium sulphate and water containing SiC particles at 1200• C. 10 wt% of this hybrid ceramic powder with dierent sized SiC particles was added to a liquid matrix alloy during a mechanical stirring between solidus and liquidus under inert conditions. Dry sliding wear tests were conducted with a pin-on-disk friction and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 34 publications
(30 reference statements)
4
16
0
Order By: Relevance
“…The positive effects of these coarse SiC particles are also seen in the study of Altinkok et al, [1] in which coarse SiC particles (>10 mm) have also improved wear resistance in Al/SiC composite system. The positive effects of these coarse SiC particles are also seen in the study of Altinkok et al, [1] in which coarse SiC particles (>10 mm) have also improved wear resistance in Al/SiC composite system.…”
Section: Wear Propertiessupporting
confidence: 55%
See 3 more Smart Citations
“…The positive effects of these coarse SiC particles are also seen in the study of Altinkok et al, [1] in which coarse SiC particles (>10 mm) have also improved wear resistance in Al/SiC composite system. The positive effects of these coarse SiC particles are also seen in the study of Altinkok et al, [1] in which coarse SiC particles (>10 mm) have also improved wear resistance in Al/SiC composite system.…”
Section: Wear Propertiessupporting
confidence: 55%
“…The wear test results confirm that SiC particles can carry load efficiently. The positive effects of these coarse SiC particles are also seen in the study of Altinkok et al, [1] in which coarse SiC particles (>10 mm) have also improved wear resistance in Al/SiC composite system. Another reason of this high wear resistance for SS/SiC composites would probably be the filling of the porosities by glassy phase as it was investigated in our previous study in the same system.…”
Section: Wear Propertiessupporting
confidence: 55%
See 2 more Smart Citations
“…They reported that the incorporation of graphite particles enhanced the wear resistance. Altinkok et al 11 analyzed the dry sliding wear behaviour of Al 2 O 3 /SiC particle reinforced aluminium based metal matrix composites fabricated by stir casting method. Mohan et al 12 investigated the dry sliding wear of Al -Gr composites and showed that graphite particles smears at the sliding interface and reduces wear, but inclusion of graphite beyond 1.5 % reduces the mechanical properties of the composite drastically.…”
Section: Introductionmentioning
confidence: 99%